Whole genome methylation combined with RNA-seq reveals the protective effects of Gualou-Xiebai herb pair in foam cells through DNA methylation mediated PI3K-AKT signaling pathway - Jia, Zijun; Mei, Jun; Zhang, Yan; Wang, Ya; Wang, Hongqin; Wang, Anlu; Xu, Fengqin; Zhou, Qingbing (Frontiers in Immunology, 2023)
Numerous studies have revealed that DNA methylation including aberrant hypomethylation and hypermethylation plays a significant role in atherosclerosis(AS). Thus, targeting the unbalanced methylation in AS could be a novel treatment strategy for AS patients. Gualou-xiebai herb pair (GXHP), a classic herb combination, have been used for the treatment of atherosclerotic-associated diseases in traditional Chinese medicine. However, the effects and underlying mechanism of GXHP on AS remain nebulous. In this study, the CCK-8 method was applied to determine the non-toxic treatment concentrations for GXHP. The formation of foam cells played a critical role in AS, so the foam cells model was established after RAW264.7 cells were treated with ox-LDL. Gas chromatography-mass spectrometry (GC-MS) and enzyme-linked immunosorbent assay (ELISA) was used to determine the contents of total cholesterol (TC), free cholesterol (FC) and inflammatory factors including IL-1β, TNF-α, and VCAM-1. Methyl-capture sequencing (MC-seq) and RNA-seq were applied to observe the changes in genome-wide DNA methylation and gene expression. Kyoto Encyclopedia of Genes and Genomes (KEGG) were performed to analyze differentially methylated genes (DMGs) and differentially expressed genes (DEGs). The targeted signaling pathway was selected and verified using western blotting (WB). The results showed that the lipids and inflammatory factors in foam cells significantly increased. GXHP significantly reduced the expression of TC, FC, and inflammatory factors. MC-seq and RNA-seq showed that GXHP not only corrected the aberrant DNA hypermethylation, but also DNA hypomethylation, thus reversed the aberrant DEGs in foam cells induced by ox-LDL. GXHP treatment may target the PI3K-Akt signaling pathway. GXHP reduced the protein levels of phosphorylated(p)-PI3K and p-AKT in foam cells. Our data suggest that treatment with GXHP showed protective effects against AS through the inhibition of DNA methylation mediated PI3K-AKT signaling pathway, suggesting GXHP as a novel methylation-based agent.